VOLUNTARY AUDIT SWITCHING : PERSPEKTIF PERATURAN MENTERI KEUANGAN N0.17/PMK.01/2008 - Nanik Niandari (Universitas Bunda Mulia, 2017)
This research aim to prove the effect of audit opinion, management changes, financial distress, company growth, and company size on voluntary auditor switching. An analytical technique employed is logistic regression analysis. This research using manufactured company listed in Indonesian Stock Exchange (BEI) which taken by purposive sampling method. During six years observations, there were 465 companies and only 74 companies (15.91%) of the observed company have changed their auditor. it was found that only audit opinion and company size variable that affect public company to change their auditor. The other three variable were not statistically significant. Keyword: Voluntary Auditor Switching, Audit Opinion, Management Changes, Financial Distress, Company Growth, and Company Size